Mental health nursing and physical health care: A cross‐sectional study of nurses' attitudes, practice, and perceived training needs for the physical health care of people with severe mental illness. (15th October 2012) - Robson, Debbie; Haddad, Mark; Gray, Richard; Gournay, Kevin
Abstract Mental health nurses have a key role in improving the physical health of people with a serious mental illness, however, there have been few studies of their attitudes or the extent of their involvement in this work. The aim of this study was to examine mental health nurses' attitudes to physical health care and explore associations with their practice and training. A postal questionnaire survey including the Physical Health Attitude Scale for mental health nurses (PHASe) was used within a UK mental health trust. The 52% (n = 585) of staff who responded reported varying levels of physical health practice; this most frequently involved providing dietary and exercise advice and less frequently included advice regarding cancer screening and smoking cessation. Having received post‐registration physical health‐care training and working in inpatient settings was associated with greater reported involvement. More positive attitudes were also evident for nurses who had attended post‐registration physical health training or had an additional adult/general nursing qualification. Overall, the attitudes of mental health nurses towards physical health care appear positive and the willingness of nurses to take on these roles needs to be recognized. However, there are areas where nurses in our sample were more ambivalent such as cancer screening and smoking cessation.